Mardi Gras: Made in China (A Review) - Miller, Cynthia (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Mardi Gras: Made in China explores the clash of cultures and economies as it follows the "bead trail" of festive baubles from the Chinese factories and production workers who make them to Bourbon Street and the Mardi Gras revelers who eagerly consume and discard them. The film traces the story behind the object, adding lives and faces to the commodity chain, and refusing to allow any of the actors in this process – those who labor, trade, own, consume, or watch – to ignore the humanity, and the indifference, involved.